Penerapan Job Description Pengurus Pondok Pesantren Yatim Piatu Dan Dhuafa Riyadhus Sholihin Bandar Lampung Dan Implikasinya Terhadap Disiplin Kerja - Mazaya Linda Shilmina; Junaidah Junaidah; Agus Pahrudin; Yetri Hasan; Sovia Mas Ayu (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This research aims to describe the application of job descriptions for boarding school administrators and their implications for performance discipline. This study uses a descriptive qualitative approach. Data collection is done by conducting interviews, observation, and documentation. Analysis of the data used in this study was carried out in stages, namely data reduction, data display, and verification and conclusions. The results of this study indicate that the application of job descriptions at the Riyadus Shalihin Islamic Boarding School in Bandar Lampung has not been carried out properly. This situation is seen from the following indicators as job assistance, job summary, duties and responsibilities, authority, work standards, working conditions, and job specifications.